The Army of the Cumberland organization, strength, casualties, 1862/1865 - Collins, Darrell L. (McFarland & Company, Inc., Publishers, 2019)
"Comprehensively researched from the 128 volumes of the reference work referred to as the Official Records, this book delves into the structural and statistical history of the Union army that served in Tennessee, Georgia and the Carolinas during the American Civil War. Details are provided regarding the army's organization, strength, and sacrifices made during its campaigns and battles"...